IndiGrid. b : transitioning into India's first independent power transmission InvIT - Agarwalla, Sobhesh Kumar; Pandey, Ajay (London : Indian Institute of Management, Ahmedabad, 2020)
This case is a sequel to the case titled "IndiGrid: Creating India's First Power Transmission InvIT (A)," which describes the structure of infrastructure investment trusts (InvITs) created and launched in Indian markets in 2017. This case describes the deal between the trust's original sponsor, Sterlite Power, and a new set of KKR-led financial investors. The new investors would first come in as an additional sponsors and eventually replace the original sponsor to become the IndiGrid trust's sole sponsor. The deal also commits the incoming investors and the eventual sponsor to buy five of the original sponsor's transmission projects as and when they become operational, with two such operational projects to be acquired immediately. The case ends with the consequence of this change on the investment manager's outlook, now owned by the incoming sponsor. The investment manager, freed from the limiting interest of the original sponsor, had to search for investment opportunities from the perspective of incoming financial investors, which included the new sponsor.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Infrastructure (Economics) -- Finance -- Case studies; Investments -- Accounting -- Case studies; Assets (Accounting) -- Case studies